(3GdOQQ GdefKhQI aj JMbjb Cf GdLSe eQcH ef Gdgjhdj hGdUhQIs - (3GdHMQGfj GdbWjaj, SdjeGf Hf CMeO Hf GdMSjf Bd YHO GdLHGQ, J (B1266 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg ajGV GdLhO (B...(3gPg hQjbGJ bdjdI hJMbjbGJ LdjdI bO hVYJgG aj JMbjb eSCdI cKQ ajgG GdcdGe (B.. (3hgj eSCdI GdLSe gd gh eQcH ef Gdgjhdj hGdUhQI Ch gh HSjW hJMbjb GdWQjbI (B...s
(3BNQgG (B:s
... (3aEf GdTjA eGde jJTNU de jhLO hGdcd dGMb ddhLhO hajg eG ajg (B.. (3Odjd gPG BNQ GdcdGe aj gPg GdQSGdI ?s
(3eHjVI GdeDda fbdgG HNWg ef eShOJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\122s
(3GdPQjYI (B8\510s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs